The Role of Information Quality, Creator Credibility, and E-Service Quality in Enhancing Customer Satisfaction and Loyalty on Tiktok Shop - Yasmin Rahima Jazuli; Popong Nurhayati; Rr. Heny Kuswanti Suwarsinah (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The precipitous expansion of social commerce has reconfigured consumer purchasing behaviour by consolidating product information, interactions with creators, and digital transactions within a singular platform. Endeavoured within this study is an examination of the influence exerted by information quality, creator credibility and e-service quality upon customer satisfaction and customer loyalty on TikTok Shop, particularly amongst consumers who procure beauty products. A quantitative approach was espoused in this study, whereby a questionnaire was disseminated to 147 consumers who have purchased beauty products via TikTok Shop. Subsequently scrutinised through variance-based structural equation modelling were the research data, so as to appraise both direct and indirect relationships amongst the research variables. Disclosed by the findings is that e-service quality and creator credibility exert a salutary and significant effect upon customer satisfaction, whereas information quality evinces no significant effect. Moreover, customer satisfaction is shown to exert a positive and significant effect upon customer loyalty and to mediate the influence of e-service quality and creator credibility upon customer loyalty. Accounted for by the research model is 68.9% of the variance in customer satisfaction and 47.9% of the variance in customer loyalty. This study concludes that customer loyalty on TikTok Shop is chiefly determined by satisfaction, which is, in turn, shaped by e-service quality and creator credibility.